5'-nucleoridase activity in sera from iraq children with leukemia - Baghdad Science Journal (مجلة بغداد للعلوم)
Enzyme activity were studied in the sera of children with leukemia than healthy children, where 31 cases were studied, including 21 cases of patients with acute lymphatic leukemia